HLAII peptide presentation of infliximab increases when complexed with TNF - Casasola-LaMacchia, Andrea; Seward, Robert Joseph; Tourdot, Sophie; Willetts, Matthew; Kruppa, Gary; Agostino, Michael J.; Bergeron, Gabrielle; Ahyi-Amendah, Nathalie; Ciarla, Andrew; Lu, Zhaojiang; Kim, Hai-Young; Hickling, Timothy P.; et al. (Frontiers in Immunology, 2022)
CD4+ T-cell activation through recognition of Human Leukocyte Antigen II (HLAII)-presented peptides is a key step in the development of unwanted immune response against biotherapeutics, such as the generation of anti-drug antibodies (ADA). Therefore, the identification of HLAII-presented peptides derived from biotherapeutics is a crucial part of immunogenicity risk assessment and mitigation strategies during drug development. To date, numerous CD4+ T-cell epitopes have been identified by HLAII immunopeptidomics in antibody-based biotherapeutics using either their native or aggregated form. Antibody-target immune complexes have been detected in patients with ADA and are thought to play a role in ADA development by enhancing the presentation of CD4+ T-cell epitopes at the surface of antigen presenting cells (APCs). The aim of this study was to investigate the effect of biotherapeutic antibody-target immune complexes on the HLAII peptide presentation of biotherapeutics in human primary monocyte-derived dendritic cells (DCs). The trimeric tumor necrosis factor (TNF) and its biotherapeutic antagonists infliximab (INFL), adalimumab (ADAL), and a single armed Fab’ were used as a model system. The HLAII immunopeptidome of DCs loaded with antagonists or their immune complexes with TNF was analyzed by trapped ion mobility time-of-flight mass spectrometry (timsTOF MS) leading to the identification of 12,000 unique HLAII-associated peptides per preparation. Anti-TNF sequences were detected at a median of 0.3% of the total immunopeptidome, against a majority background of peptides from endogenous and media-derived proteins. TNF antagonist presentation spanned the variable and constant regions in a widespread manner in both light and heavy chains, consistent with previously discovered HLAII peptides. This investigation extends the collection of observed HLAII peptides from anti-TNF biotherapeutics to include sequences that at least partially span the complementary determining regions (CDRs), such as the LCDR1 for both INFL and ADAL. Although antagonist presentation varied significantly across donors, peptides from both bivalent antagonists INFL and ADAL were more highly presented relative to the Fab’. While TNF immune complexes did not alter overall HLAII presentation, a moderate increase in presentation of a subset of peptide clusters was observed in the case of INFL-TNF, which included HCDR2, HCDR3 and LCDR2 sequences.